2023
DOI: 10.1002/jcla.24984
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free DNA extraction from urine of lung cancer patients and healthy individuals: Evaluation of a simple method using sample volume up‐scaling

Tilman Ruppert,
Andreas Roth,
Jens Kollmeier
et al.

Abstract: BackgroundUrine holds promise as a source for cell‐free DNA (cfDNA) analysis of cancer genetics due to its nature as a self‐collectable biospecimen available in large quantities. However, pre‐analytical variables such as preservation of cfDNA or efficiency of up‐scaling specimen volume need to be better explored to increase analysis sensitivity.Patients and MethodsInitially effects of pH levels on cfDNA stability of urine preserved with EDTA were investigated in three healthy probands. Furthermore, the efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…cfDNA in urine has shown great potential in noninvasive diagnosis. Urine is an ideal biomaterial for the study of urological diseases due to its direct contact with the urinary system and convenient collection of sufficient volume ( Ruppert et al, 2023 ). Research has shown significantly higher levels of urine cfDNA (ucfDNA) in patients with urinary tumors compared to healthy individuals ( Nikanjam et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cfDNA in urine has shown great potential in noninvasive diagnosis. Urine is an ideal biomaterial for the study of urological diseases due to its direct contact with the urinary system and convenient collection of sufficient volume ( Ruppert et al, 2023 ). Research has shown significantly higher levels of urine cfDNA (ucfDNA) in patients with urinary tumors compared to healthy individuals ( Nikanjam et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown significantly higher levels of urine cfDNA (ucfDNA) in patients with urinary tumors compared to healthy individuals ( Nikanjam et al, 2022 ). Nevertheless, the clinical application of ucfDNA is relatively rare, possibly due to its sensitivity to environmental conditions (e.g., temperature and pH level of preservation solution) ( Kim et al, 2023 ; Ruppert et al, 2023 ), which makes it easier to degrade rapidly, resulting in inadequate concentrations for downstream analysis ( Nel et al, 2023 ) compared to blood-derived cfDNA. Therefore, the weaker stability makes ucfDNA analysis more susceptible to complex preanalytical variables, highlighting the importance of establishing a consensus on ucfDNA experimental procedures.…”
Section: Introductionmentioning
confidence: 99%